Effectiveness of STEM integration in science learning to improve problem solving skills of junior high school students - Herliantari, Hesti (Jurnal Inovasi Guru Indonesia, 2024)
Education at the junior high school level plays a crucial role in developing problem-solving skills needed by students to face challenges in the 21st century. The STEM (Science, Technology, Engineering, and Mathematics) approach, applied through the Project-Based Learning (PjBL) model, is considered effective in enhancing students' critical and creative thinking skills, which are integral parts of problem-solving skills. This article aims to examine the effectiveness of integrating STEM in science learning at junior high schools to improve students' problem-solving skills. The results of the study show that the implementation of the PjBL-STEM model not only enhances students' understanding of science concepts but also develops their problem-solving skills through project-based learning experiences that involve collaboration and the application of concepts in real-world contexts. Despite challenges in its implementation, especially related to teacher readiness and limited resources, the application of this model has proven to have a positive impact in preparing students for real-life challenges. This study suggests the need for ongoing training for teachers and the improvement of STEM-based learning facilities in junior high schools.